Algorithm to Estimate Sorghum Grain Number from Panicles Using Images Collected with a Smartphone at Field-Scale - G. N. Santiago; A. J. P. Carcedo; L. Marziotte; I. A. Ciampitti (Kansas Agricultural Experiment Station Research Reports, 2023)
An estimation of on-farm yield before harvest is important to help farmers make decisions about additional input use, time to harvest, and options for end uses of the harvestable product. However, obtaining a rapid assessment of on-farm yield can be challenging, especially for a sorghum (Sorghum bicolorL.) crop due to the complexity of counting the total number of grains in a panicle at field-scale. One alternative to reduce labor is to develop a rapid assessment method employing computer vision algorithms. Computer vision has already been utilized to account for the number of grains within a panicle, yet it has only been tested under controlled conditions. The objective of this study was to estimate the number of grains in a sorghum panicle using imagery data captured from a smartphone device at field-scale. During the pre-harvest season, sorghum panicles of several commercial hybrids were photographed in the field. Later, the plants corresponding to those panicles were harvested to determine the final number of grains, to develop a benchmarking dataset. Using Python language and the OpenCV library, each image was filtered, blurred, and contours were applied to estimate the number of grains in each sorghum panicle. The absolute mean difference obtained using the algorithm output for the observed and the estimated number of grains was 570 (root mean square percentage error = 53%).
Keywords: computer vision; grain counting; sorghum